Perlindungan Hukum Bagi Korban Dalam Peralihan Hak Atas Tanah Secara Melawan Hukum - Al Farabi, Maulana Ahmad; Lyanthi, Merline Eva (Media Hukum Indonesia (MHI), 2025)
Illegal transfer of land rights is a developing and serious problem in Indonesia's land management system. This problem often involves fraud, document forgery, misuse of authority, and even complicity with corrupt officials, leading in the loss of land rights rightfully owned by citizens. In addition to causing the victims to suffer actual and intangible damages, these transgressions also compromise core legal precepts such as justice, legal certainty, and the defense of fundamental rights protected by the Constitution. The purpose of this study is to thoroughly investigate the types of legal protection that victims can obtain through non-litigation processes like mediation, administrative complaints, and legal aid, as well as through litigation channels including civil lawsuits, criminal reports, and administrative disputes.  By analyzing court decisions, this study uses a legislative, intellectual, and case-based approach to the normative legal method. The study's findings demonstrate that even though the Indonesian legal system has offered a variety of safeguards, victims continue to encounter a number of challenges, including convoluted processes, restricted access to legal aid, and widespread maladministration.  Therefore, to ensure that the preservation of land rights is not only normative but can be actually implemented in tangible terms in social life, it is imperative to promote public legal literacy, reform the land bureaucracy, provide access to legal assistance, and fortify law enforcement authorities.